CLINIC, DIAGNOSIS AND TREATMENT OF NON-HODGKIN'S LYMPHOMA OF THE THYROID GLAND - Константинова, Наталья Николаевна; Мозес, Вадим Гельевич; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2022)
Thyroid lymphoma refers to rare forms of non-Hodgkin's extranodal lymphomas.A characteristic feature of lymphoma in our cases was the rapid progression of symptoms of compression of the neck and mediastinum, which required immediate diagnosis and urgent initiation of treatment. Surgical intervention on the thyroid gland made it possible to stop life-threatening syndromes and made it possible to obtain material for morphological verification of the tumor. Specialized treatment made it possible to obtain stabilization in the first case, and remission in the second. Although this tumor is characterized by local spread and the development of localized recurrence, thyroid lymphoma belongs to an unfavorable prognostic group. According to literature data, the use of a combination of radiation and chemotherapy increases the overall effect of treatment compared with the use of chemotherapy alone or a combination of chemotherapy and surgical treatment. The use of radiation therapy in combination with chemotherapy reduces the likelihood of disease progression compared to other treatment options. Further experience in the treatment of such patients will make it possible to use a combination of radiation and chemotherapy in practice.
Keywords: thyroid gland; lymphoma; clinic; treatment